2007
DOI: 10.1038/sj.ejcn.1602927
|View full text |Cite
|
Sign up to set email alerts
|

Dietary diversity scores can be improved through the use of portion requirements: an analysis in young Filipino children

Abstract: Objectives: Early childhood malnutrition is a pressing international concern which dietary diversity scores (summary scores of food groups in the diet) may be helpful in addressing. We explored three current research needs surrounding diversity scores: the impact of portion size on score function, the relationship of scores to nutrient adequacy and density and the ability of scores to function as screening tools. Subjects/Methods: 1810 children, age 24 months. Cross sectional study of a birth cohort. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 16 publications
(30 reference statements)
1
44
0
3
Order By: Relevance
“…A recent study among women in five low-income nations showed that across study sites (Burkina Faso, Mali, Mozambique, Bangladesh and the Philippines), the correlations between the 15 g minimumdiversity score and nutrient intakes were at least 27 %, 20 %, 10 %, 5 % and 21 % higher than those between the 1 g minimum-diversity score and nutrient intakes, respectively (12) . A study among non-breast-feeding children in the Philippines showed correlation coefficients were at least 22 % higher when a 10 g minimum food group intake was imposed (10,13) . Similar comparisons showed differences ranging from 2 % to 17 % among young children in Madagascar (11) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study among women in five low-income nations showed that across study sites (Burkina Faso, Mali, Mozambique, Bangladesh and the Philippines), the correlations between the 15 g minimumdiversity score and nutrient intakes were at least 27 %, 20 %, 10 %, 5 % and 21 % higher than those between the 1 g minimum-diversity score and nutrient intakes, respectively (12) . A study among non-breast-feeding children in the Philippines showed correlation coefficients were at least 22 % higher when a 10 g minimum food group intake was imposed (10,13) . Similar comparisons showed differences ranging from 2 % to 17 % among young children in Madagascar (11) .…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the developed nations, only a few studies in less-developed nations have imposed a minimum food group intake amount when defining food group 'consumers' (1,(8)(9)(10)(11)(12) . An assessment of some of these studies shows that imposing a standard 10 g or 15 g minimum intake produces a DDS that not only has a stronger association with nutrient intake but also shows a greater resilience to energy adjustment and has a better ability to differentiate children or women with different intake levels of nutrient adequacy (10)(11)(12)(13) . While the use of a fixed minimum amount across all food groups is easy to apply, such a set minimum may not consider varying contributions of food groups to nutritional needs.…”
mentioning
confidence: 99%
“…Simple counts of the number of food groups consumed have been shown in developing country settings to be adequate proxy indicators of micronutrient intake among children (8)(9)(10)(11)(12) and also among adults in diverse settings (13)(14)(15). Although the use of food group diversity indicators (FGI) 11 has shown promise in different settings, methodologies for indicator construction have varied (16).…”
Section: Introductionmentioning
confidence: 99%
“…This lack of knowledge, combined with the fact that multiple micronutrient deficiencies often occur simultaneously has led to increasing interest in dietary diversity as a measure of diet quality and proxy for overall micronutrient intake (Arimond and Ruel 2004;FAO 2012;Kennedy et al 2011;Ruel 2003). Individuals scoring poorly on dietary diversity scores have often not consumed sufficient animal source foods, fruits, vegetables and legumes (Daniels et al 2007;Moursi et al 2008;Powell 2012). The importance of these types of food for micronutrient intake helps to explain why dietary diversity scores are usually associated with better nutritional status (Kennedy et al 2011).…”
Section: Micronutrient Intake and Dietary Diversitymentioning
confidence: 99%